Workshop Kreatif Mading Sekolah untuk Siswa SD Desa Sinar Bhakti - Rida Oktarina; Nova Alia; Tesha Caroline; Cindy Hedi Wardana; Palupi Indah Sari (Jurnal Nusantara Berbakti, 2025)
The creative workshop on designing school bulletin boards is a community service activity aimed at enhancing the collaboration and creativity skills of students at SD 168 in Sinar Bhakti Village. The main issue identified is the lack of effective learning media to stimulate teamwork and creativity among students. This program was designed to train students in designing school bulletin boards as a medium for expression and interactive learning. The activity was carried out in several stages: initial observation to identify students' needs, theoretical training on the basic concepts of bulletin board creation, hands-on group practice to produce projects, and evaluation of the final results and students’ teamwork processes. The results showed that students not only improved their collaboration skills but also successfully created bulletin boards that were attractive and relevant to the given themes. Furthermore, the program increased students' confidence in presenting their work in public. The positive impact of this activity is reflected in the heightened enthusiasm of students for project-based learning activities. Thus, this program makes a significant contribution to the sustainable development of collaboration and creativity potential among students at SD 168 in Sinar Bhakti Village.